Challenging conventional risk assessment with respect to human exposure to multiple food contaminants in food: A case study using maize. Issue 1 (1st October 2015) - Clarke, R.; Connolly, L.; Frizzell, C.; Elliott, C.T.
Highlights Multiple chemical contaminants threaten the safety of many food commodities. Cytotoxicity was found at concentrations representing legal limits. The most cytotoxic mixture was (tertiary mycotoxins plus Cd/As/CP/PM). Synergy was evident at concentrations contaminating maize above legal limits.